First report of Athelia rolfsii (=Sclerotium rolfsii) associated with foot rot disease of Chrysanthemum morifolium in India - Mahadevakumar, S; Sarma, P V S R N; Danteshwari, C; Joy, Josna; Mahesh, M; Mamathabhanu, L S; Santhosh, C R; Chandranayaka, S (Plant disease, 2023)
Chrysanthemum morifolium L. is an important flower crop grown in different parts of Karnataka for its striking cut flowers and international market value. During a field survey (Mysore district, Karnataka, February, 2022), chrysanthemum fields were found infected with foot rot disease. The presence of white mycelial structures with sclerotia were recorded near the stem-soil interface. The disease incidence ranged 10-12% measured in an area of approximately 10 hectares. The infected plants showed quick wilt, yellowing and toppling of the entire plant. Infected plants from Doddamaragowdanahally and Rayanahally (n=15) were collected and associated fungal pathogen isolated after surface sterilization with NaOCl (1%) on potato dextrose agar (PDA) amended with chloramphenicol (50 mg/L). Fungal mycelia developed from the infected tissues were inoculated on to fresh PDA plates to obtained pure cultures for further identification. Fungal colonies with dense, aerial whitish-cottony mycelia with uniformly globoid sclerotia (0.284.2 mm) were observed after 15 days of incubation (28 ± 2°C). Sclerotia were white in the beginning and turned brown at maturity. The average number of sclerotia produced per plate ranged from 240 to >480 (n = 10). To further to confirm the identity of the isolates, two representative isolates (CmSr1 and CmSr2) was subjected to molecular identification based on ITS-rDNA sequences. Briefly, genomic DNA was isolated from 12 day old cultures using the CTAB method and ITS-rDNA was amplified using ITS1-ITS4 primers (White et al., 1990). An expected amplicon of >650 bp (ITS) was obtained and later sequenced from both the directions. The consensus sequences were analysed through nBLAST search which revealed that 100% sequence similarity with reference sequences of Athelia rolfsii (S. rolfsii) from GenBank database (MT127465, MN974137, KC292637; identity 656/656; 0 gaps). A phylogenetic tree obtained by the neighbor-joining method using MEGAX shared a common clade with the reference sequences retrieved and computed, thus confirming the identification based on sequence analysis and molecular phylogeny. The representative sequence of A. rolfsii isolates CmSr1 and CmSr2 isolates deposited in GenBank with Accession nos. ON456153 and ON456154, respectively. Based on etiology, morphological, cultural and molecular data the pathogen was identified as Athelia rolfsii (Curzi) Tu & Kimbrough (Syn: Sclerotium rolfsii Sacc.) (Mordue, 1974; Mahadevakumar et al., 2016, 2018). Plants (n=60) were inoculated with sclerotial bodies (2 sclerotia/plant) near stem soil interface under green house and covered with polythene bags (at 27 ± 2°C and 80% RH). Non-inoculated plants (n=20) served as controls. The development of foot rot disease was observed eight days after inoculation. A total of 48 plants showed the foot rot symptoms and 12 inoculated plants and control plants remained healthy. The identity of the fungus was confirmed by morphological and cultural characters after re-isolation. C. morifolium is an important flower crop in Karnataka. S. rolfsii is known to be associated with blight and collar rot of Chrysanthemum spp. from Kerala (Beena et al., 2002) but no species (host) identity provided. Therefore, to the best of our knowledge, this is the first report of foot rot disease caused by Athelia rolfsii on C. morifolium in India. Early diagnosis of this disease will help the farmers to adopt suitable management practices to avoid loss.